The Influence of Cement Spacer Thickness on Retentive Strength of Monolithic Zirconia Crowns Cemented with Different Luting Agents (A Comparative in-vitro Study) - Reyam H. Ali1 , Mohammed Kassim2 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aims of Study: to evaluate and compare the retentive strength and the failure-modes of monolithic zirconiacrowns with different cement spacer thickness, cemented with two different types of luting agents.Materials and Methods: Forty sound maxillary first premolar teeth were divided into two main groups(n=20): Group A: cement spacer thickness of 80?m; Group B: cement spacer thickness of 120?m. Thegroups were further subdivided into two subgroups (n=10): (A1, B1) cemented with Panavia F2.0 resincement; (A2, B2) cemented with Riva luting plus RMGIC. All the teeth were prepared to receive monolithiczirconia crowns with the following features: (6º convergence angle, 0.8mm deep chamfer finishing line,4mm axial wall height with planar occlusal reduction). Afterwards, the teeth were scanned and the crownswere fabricated and cemented. Zirconia crowns were pulled-out along its path of insertion using universaltesting machine. Failure stresses were calculated in MPa. Failure-modes was assessed using magnifyinglens (2.5X).Results: The highest mean retentive values (in Mpa) was recorded by subgroup B1 (8.651); followed bysubgroup B2 (7.765); subgroup A1 (7.309) and subgroup A2 (6.875). Independent t-test showed a statisticallysignificant difference between A1 and B1 subgroups. Concerning the failure-mode, the majority of samplesrevealed adhesive failure between teeth and cement.Conclusion: All the tested crowns have mean retentive values within the clinically acceptable limit,increasing cement space resulted in a significant increase in the retention when Panavia F2.0 used as a lutingagent, while, it has no significant effect on the retention when RIVA luting plus was used.